How to live when a loved one dies: healing meditations for grief and loss - Nhất Hạnh, Thích (Parallax Press, 2021)
"In this book that offers relief to anyone moving though intense grief and loss, Zen Master Thich Nhat Hanh shares accessible, comforting words of wisdom on how to transform our suffering in the face of death"--